Utilization of Solar Cell Power Generation System to Reduce Fuel Consumption on MT. Hendropriyono III - Agus Priyanto; Diah Zakiah; Damayanto Purba (Meteor STIP Marunda, 2023)
The use of fossil fuels as the primary energy source for ship power generation has led to increasing environmental concerns, particularly regarding greenhouse gas emissions and fuel depletion. This study investigates the utilization of a solar cell power generation system as an alternative energy source to reduce fuel consumption on MT. Hendropriyono III, a tanker vessel operated by PT. Cakra Manunggal Semesta. Employing a Research and Development (R&D) methodology according to Sugiyono's model, a prototype of a solar photovoltaic (PV) system was designed, validated by an expert, and tested. The prototype consisted of a 60W monocrystalline solar panel, a solar charger controller (SCC), a 12V/5Ah battery, and a 300W inverter. Testing over three days under overcast conditions in Jakarta yielded an average voltage output of 12.21–12.57V during peak sunlight hours (07:00–15:00) and sustained a 6W AC lamp load for approximately 10 hours. Expert validation scored the prototype at 100% suitability, while a trial assessment by 15 marine engineering cadets rated it at 96.25% ("suitable"). Scaling the design for onboard application, two SunPower E20-435-COM panels (435 Wp each) installed on the wing deck (123.24 m²) would generate approximately 4.35 kWh per day under an assumed 5-hour peak sun equivalent, sufficient to supply navigation deck lighting loads of 3.953 kWh/day. The resulting reduction in diesel generator load from 440 kW to 433 kW during anchorage translates to an estimated annual fuel saving of 11,542 liters of LSFO, equivalent to approximately Rp 191,597,200 per year, with a return on investment period of approximately 1.9 months against an initial installation cost of Rp 30,572,000. These findings demonstrate that solar PV integration on vessels operating in Indonesian waters is technically feasible and economically advantageous, supporting IMO MARPOL Annex VI emission reduction objectives.